1989
DOI: 10.1111/j.1365-2842.1989.tb01381.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between clinical and histological evaluations of the peri‐implant gingiva around the single‐crystal sapphire endosseous implant

Abstract: The correlation between clinical periodontal parameters and histological structure of the gingiva around a single-crystal sapphire implant has been evaluated in two volunteer subjects. The implants had functioned after 6 years as the distal abutment of implant bridges in the Kennedy class II mandible. First, clinical evaluation was performed (gingival bleeding index, crevicular fluid volume, plaque index and probing depth) of the gingiva around the implant and natural teeth abutments and then a small piece of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 8 publications
3
9
0
Order By: Relevance
“…As a consequence, the soft-tissue margin receded, and bone resorption occurred. These observations confirm previous; findings from animal experiments and clinical trials with single-crystal sapphire implants (Akagawa et al, 1989;Fartash et al, 1990;Arvidson et al, 1991Arvidson et al, , 1996.…”
Section: Clinical Studiessupporting
confidence: 82%
“…As a consequence, the soft-tissue margin receded, and bone resorption occurred. These observations confirm previous; findings from animal experiments and clinical trials with single-crystal sapphire implants (Akagawa et al, 1989;Fartash et al, 1990;Arvidson et al, 1991Arvidson et al, , 1996.…”
Section: Clinical Studiessupporting
confidence: 82%
“…However, there is some controversy in the literature regarding the significance of measuring probing depths around dental implants. It has been reported that probing depths are consistently greater around stable implants when compared to natural teeth (Akagawa et al 1989; Apse et al 1989). The altered probing depths of implants may be directly related to bone loss, whereas changes around teeth with attached dentogingival fibers may rather be related to attachment loss and changes in inflammation (Schou et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…For most authors, these fibres run a course more or less parallel to the implant surface. This observation was made both in human subjects (Akagawa et al 1989; Chavrier et al 1994; Liljenberg et al 1996, 1997) and in animal models: monkeys (Listgarten & Lai 1975; Gotfredsen et al 1991) and dogs (Berglundh et al 1991; Ericsson et al 1995; Abrahamsson et al 1996; Cochran et al 1997; Çomut et al 2001).…”
Section: Connective Tissue Adhesionmentioning
confidence: 99%